Expecting the best or fearing the worst: Discrepancies between self‐rated health and frailty in an ageing Irish population. Issue 3 (11th February 2022) - Calvey, Bill; McHugh Power, Joanna; Maguire, Rebecca
Abstract : Objectives: Ageing populations have the propensity to rate their health status more inaccurately than their younger counterparts. As a result, we (1) devised a metric which categorized older adults into groups based on the discrepancy between their self‐rated health (SRH) and Frailty Index (FI) scores, and (2) investigated which factors predict group membership. Design: A cross‐sectional design was employed using data from The Irish Longitudinal Study of Ageing (TILDA). Methods: A health asymmetry metric was derived: this categorized 6907 participants (aged 50+ years) into three groups: 'health pessimistic' where participants underestimated their healthiness, 'health realistic' where participants accurately assessed their health, and 'health optimistic' where participants overestimated their healthiness. A multinomial logistic regression modelled the ability of a set of sociodemographic, psychosocial, and health behaviour variables in predicting membership of these categories. Results: A significant proportion of the study population were categorized as 'health realistic' ( 69%). The prevalence rates of health optimistic individuals increased in older age groups, and conversely, health pessimistic rates decreased in older age groups. Most notably, psychosocial factors significantly predicted being health pessimistic: such as anxiety (OR = 1.03), loneliness (OR = 1.04), and decreased social connectedness (OR = 0.87). However, less clear sociodemographic, psychosocial, and health behaviour associations were found for being health optimistic. Conclusion: Health asymmetry is a useful method of identifying at‐risk individuals for inaccurate SRH. The ability of this metric to predict clinical mental health outcomes should be investigated.